Transportation programming model for gas network - Yahyazadeh, A. (Asian Research Publishing Network, 2016)
The normal practices in transporting gas from sources to consumers are using gas pipeline. One option to optimize the transportation cost is to model the distribution pipeline using mathematical programming. The aim of this paper is to present the transportation programming model for minimizing the cost of gas transportation. The model has included three units, gas production sites, refinery stations and consumers or cities. The model solved by two parts. The first part is gas transportation from production sites to refinery stations and the second part is gas transportation from refinery stations to consumers. The Vogel method is used to solve the model. The Iranian natural gas network is used as case study. The data of the network was collected from Iranian Natural Gas Company directly. The results of the comparison between two parts of the model and case study reveal that the Iranian natural gas network could save approximately 7 percent of the current cost by using the results of the model. Â© 2006-2016 Asian Research Publishing Network (ARPN).